Predicting accelerated fetal growth in pregnancy: beyond maternal hyperglycemia – The role of prothymosin-α, inflammatory cytokines, and angiogenic factors - Maria Mirabelli; Marta Greco; Stefano Iuliano; Francesco Dragone; Eusebio Chiefari; Daniela Foti; Antonio Brunetti (Journal of Clinical & Translational Endocrinology, 2025)
Aim: This study investigates prothymosin-α (ProT-α), an immunomodulatory protein, as a potential biomarker for insulin resistance in gestational diabetes (GDM), and as a predictor of fetal growth by 20 weeks of gestation (wg). Methods: Forty-six women with singleton pregnancies were classified into GDM (n = 8) and normal glucose tolerance (NGT; n = 38) groups based on 75 g OGTT results. Maternal glucose, insulin, cytokines, and ProT-α levels were measured, and fetal growth was assessed by ultrasound at 20 wg, focusing on abdominal circumference (AC) and estimated fetal weight (EFW) percentiles. Results: Women with GDM were older, had a higher BMI, glucose, and insulin levels, with fetuses showing higher AC and EFW percentiles. IL-8, TNFα, and IL-1α were lower in the GDM group, while ProT-α was also lower but not significantly. ProT-α inversely correlated with EFW percentiles, independent of GDM. Regression analysis identified 2-hour post-load glucose, VEGF, and EGF as positive predictors of fetal growth acceleration, while IL-10 and ProT-α were negative predictors. Conclusions: Fetal growth is influenced by maternal glucose, inflammation, and angiogenesis. ProT-α may serve as an independent biomarker for predicting fetal growth in early pregnancy, suggesting further investigation into its role in GDM, obesity, and insulin resistance.